A mechanistic model for hydraulic behaviour and nitrogen dynamics in a vertical flow constructed wetland treating septage - Tan, Yee Yong (Curtin University, 2016)
A mechanistic model has been developed to simulate the hydraulic behaviour and nitrogen dynamics of a vertical flow constructed wetland treating septage. The proposed model, VF_Sep, consists of a hydraulic module, transport module and a bio-kinetics module. VF_Sep successfully predicted the effluent flux and the associated concentration of ammonium and nitrate. The simulated results indicated that nitrification and adsorption were the major removal mechanisms of ammonium, which were greatly affected by the hydraulic behaviour.